Effect on skin hydration of using baby wipes to clean the napkin area of newborn babies: assessor-blinded randomised controlled equivalence trial - Lavender Tina; Furber Christine; Campbell Malcolm; Victor Suresh; Roberts Ian; Bedwell Carol; Cork Michael J (BMC, 2012)
Abstract Background Some national guidelines recommend the use of water alone for napkin cleansing. Yet, there is a readiness, amongst many parents, to use baby wipes. Evidence from randomised controlled trials, of the effect of baby wipes on newborn skin integrity is lacking. We conducted a study to examine the hypothesis that the use of a specifically formulated cleansing wipe on the napkin area of newborn infants (<1 month) has an equivalent effect on skin hydration when compared with using cotton wool and water (usual care). Methods A prospective, assessor-blinded, randomised controlled equivalence trial was conducted during 2010. Healthy, term babies (n = 280), recruited within 48 hours of birth, were randomly assigned to have their napkin area cleansed with an alcohol-free baby wipe (140 babies) or cotton wool and water (140 babies). Primary outcome was change in hydration from within 48 hours of birth to 4 weeks post-birth. Secondary outcomes comprised changes in trans-epidermal water loss, skin surface pH and erythema, presence of microbial skin contaminants/irritants at 4 weeks and napkin dermatitis reported by midwife at 4 weeks and mother during the 4 weeks. Results Complete hydration data were obtained for 254 (90.7 %) babies. Wipes were shown to be equivalent to water and cotton wool in terms of skin hydration (intention-to-treat analysis: wipes 65.4 (SD 12.4) vs. water 63.5 (14.2), p = 0.47, 95 % CI -2.5 to 4.2; per protocol analysis: wipes 64.6 (12.4) vs. water 63.6 (14.3), p = 0.53, 95 % CI -2.4 to 4.2). No significant differences were found in the secondary outcomes, except for maternal-reported napkin dermatitis, which was higher in the water group (p = 0.025 for complete responses). Conclusions Baby wipes had an equivalent effect on skin hydration when compared with cotton wool and water. We found no evidence of any adverse effects of using these wipes. These findings offer reassurance to parents who choose to use baby wipes and to health professionals who support their use. Trial registration Current Controlled Trials ISRCTN86207019